Beberapa Kecerdasan Kontemporer (Analisa Pemikiran Howard Gardner tentang Kecerdasan Majemuk) - Humaisi, M. Syafiq (FKIP Universitas Wisnuwardhana, 2023)
IQ is still a measure of intelligence in almost all educational institutions. The smart children, are those whose report card scores are good, their grade point average is above average. In general, the paradigm of intelligence adopted by society, especially our world of education today, can be divided into two types, namely the old paradigm and the new paradigm. First, IQ as a measure of intelligence. Second, the theory of intelligence which offers a broader view, that everyone has several types of intelligence that are sustainable and can be developed for lifetime. How one can use the intelligences to solve problems and create products in a conducive and natural environment.